XOHISH-ISTAK MAYLINI SHAKLLANTIRUVCHI VOSITALAR FRANSUZ TILI MIQIYOSIDA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The main part of the structure of the language is occupied by the verb group.The meaning of a verb in a sentence shows an action taking place in space and time. In the French language, various techniques are actively involved in the formation of the subjunctive mood. The purpose of the scientific article is to find out the role and functions of the means used together with the subjunctive mood.
Keywords: le subjonctif, Le présent du subjonctif, subsequent conjunctions, les verbs impersonnels, les locution.